Meaningful learning: Motivations of older adults in serious games - Cardona, Johnny Salazar (2023)
Social sustainability is the generation of significant behaviors through balanced levels of education, learning and awareness so that the population has a good standard of living, achieves self-improvement and supports society. This can be achieved with various strategies, one of which is learning through games, which has gained popularity in recent years due to positive results. This is effectively achieved through serious gaming, which is growing steadily, mostly in education and healthcare. This type of strategy has been typically used in young populations with a transparent interaction with technological processes that facilitate its application. However, one cannot neglect other populations such as the elderly, who may experience a technology gap and may not perceive this type of initiative in the best light. The purpose of this article is to identify the different motivations that can encourage older adults to use serious games to encourage learning processes through technology. For this purpose, different previous research on gaming experiences with older adults has been identified, from which it was possible to categorize a series of factors that motivate this population. Subsequently, we represented these factors by means of a model of motivation for the elderly and, to be able to use it, we have defined a set of heuristics based on this model. Finally, we used the heuristics by means of a questionnaire to evaluate the design of serious gaming for older adults, obtaining positive results for the use of these elements to guide the design and construction of serious games for learning in older adults.